2011
DOI: 10.1037/a0024742
|View full text |Cite
|
Sign up to set email alerts
|

Action compatibility effects are hedonically marked and have incidental consequences on affective judgment.

Abstract: Recent results from Cannon, Hayes, and Tipper (2010) have established that the Action Compatibility Effect (ACE) is hedonically marked and elicits a genuine positive reaction. In this work, we aim to show that the hedonic marking of the ACE has incidental consequences on affective judgment. For this, we used the affective priming paradigm principle (for a review, see Musch & Klauer, 2003): participants have to respond, as quickly as they can, regarding the pleasantness or unpleasantness character of a target w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 17 publications
1
16
1
Order By: Relevance
“…The results were taken as first empirical evidence for the aversive nature of conflicts. Comparable results have also been reported for action compatible common household objects (Brouillet et al, 2011). In a further study (Fritz and Dreisbach, in press) the authors investigated whether the aforementioned conflict priming effect was actually due to the affective valence inherent in conflict primes or simply due to a match of processing fluency between prime and target (since positive stimuli as well as congruent primes can be processed faster than negative stimuli and incongruent primes).…”
Section: The Affective Value Of Conflictssupporting
confidence: 81%
“…The results were taken as first empirical evidence for the aversive nature of conflicts. Comparable results have also been reported for action compatible common household objects (Brouillet et al, 2011). In a further study (Fritz and Dreisbach, in press) the authors investigated whether the aforementioned conflict priming effect was actually due to the affective valence inherent in conflict primes or simply due to a match of processing fluency between prime and target (since positive stimuli as well as congruent primes can be processed faster than negative stimuli and incongruent primes).…”
Section: The Affective Value Of Conflictssupporting
confidence: 81%
“…We focused on task repetitions, as these most closely resemble the task conditions under which the affective signatures of conflict processing have previously been investigated (Brouillet, Ferrier, Grosselin, & Brouillet, 2011; Dreisbach & Fischer, 2012; Fritz & Dreisbach, 2013; Fritz & Dreisbach, 2014; Schouppe et al, 2015). If incongruent (relative to congruent) trials are indeed experienced as more negative, due to either their higher control demands (Botvinick, 2007) or lower outcome expectancy (Alexander & Brown, 2011; Silvetti et al, 2011), we expected these trials to elicit lower ACC activation during subsequent affectively matching negative picture presentations, but higher ACC activations during the presentation of affectively non-matching positive picture presentations, and vice versa for congruent trials.…”
Section: Resultsmentioning
confidence: 99%
“…In the wake of Botvinick (2007)’s proposal, a growing number of behavioral studies confirmed its first assumption, namely that cognitive conflicts appear to be experienced as aversive events (Brouillet, Ferrier, Grosselin, & Brouillet, 2011; Dignath & Eder, 2015; Dreisbach & Fischer, 2012; Fritz & Dreisbach, 2013, 2015; Schouppe et al, 2012; 2015; for a review, see Dreisbach & Fischer, 2015). For example, Dreisbach and Fischer (2012) investigated this by combining a classic color Stroop task (Stroop, 1935) with an affective priming paradigm (Fazio, 2001).…”
Section: Introductionmentioning
confidence: 98%
“…First, conflict and errors trigger negative affect. The negative affective valence of errors (e.g., Aarts, De Houwer, & Pourtois, 2012 and of stimulus and response conflict has been demonstrated in several studies (e.g., Braem et al, 2017;Brouillet, Ferrier, Grosselin, & Brouillet, 2011;Dreisbach & Fischer, 2012a;Fritz & Dreisbach, 2013) and is discussed in several reviews (Botvinick, 2007;Dreisbach & Fischer, 2015, 2016Inzlicht, Bartholow, & Hirsh, 2015;Saunders et al, 2017;van Steenbergen, 2015).…”
Section: Conflict Monitoring As Affective Monitoring?mentioning
confidence: 97%